Sustainable resilience strategy: unleash the micro-businesses's potential in the digitalization and sustainability era - Eriana Astuty; Ivan Diryana Sudirman; Rudy Aryanto (Cogent Business & Management, 2024)
This research aims to (1) build and predict a sustainable business model to support micro-business in developing its potential in facing the challenges of the dual transition era (digitalization and sustainability); (2) explore opportunities and challenges for sustainable business models in the creative craft, fashion, food and beverage industry sectors. This research used a mixed methods approach on 381 micro and small businesses in Indonesia, utilizing an explanatory sequential design. The study revealed that aligning internal resources with responsive strategies can form sustainable resilience strategies (SRS) that are reflected in survival, continuity, reorientation, and synergy. These SRS strategies significantly impact micro-businesses in meeting the challenges of adopting digital technology in their business operations. Moreover, to meet the challenges of a sustainable business model, micro-businesses must have a high orientation to achieving sustainable development goals first, then SRS can mediate them so that sustainable business practices are realized, which have a lasting impact on sustainable business performance. Overall, This study recommends that micro-businesses adopt a sustainable resilience strategy and campaign the SDG agenda through digital technology adoption. This research provides practical insights for micro-businesses in exploring sustainable business opportunities and challenges. It also benefits stakeholders such as industry, universities, science and technology parks as an integrated innovation platform, and the government in shaping policies and regulations related to digitalization and sustainability. Resilience has been previously studied as an input, process, or outcome. This study has discovered resilience as a sustainable strategy for micro-businesses, which is the novelty of this study.
Keywords: 650; Digital technology adoption; sustainable development goals; sustainable resilience strategy; sustainable entrepreneurial practices; sustainable business performances; entrepreneurial competence; entrepreneurial orientation